Genetic characterisation of Giardia duodenalis in dairy cattle in Brazil - Paz e Silva, Flávio Medeiros [UNESP]; Lopes, Raimundo Souza [UNESP]; Araújo Jr., João Pessoa [UNESP] (Biology Centre, AS CR, 2012)
The intestinal protozoan parasite Giardia duodenalis (Lambl, 1859) Kofoid & Christiansen, 1915 [syn. Giardia intestinalis and Giardia lamblia] has emerged as a widespread enteric pathogen in humans and domestic animals. In recent years, G. duodenalis has been found in cattle worldwide and longitudinal studies have reported cumulative prevalence of 100% in some herds. In the present study, we determined the prevalence and genetic characterisation of G. duodenalis in 200 dairy cattle from 10 dairy farms in São Paulo state, Brazil. All faecal specimens were screened for the presence of G. duodenalis using microscopy examination, enzyme immunoassay (EIA) and polymerase chain reaction (PCR). DNA was extracted from faecal samples and G. duodenalis were identified by amplification of the small subunit ribosomal (SSU-rDNA) and glutamate dehydrogenase (GDH) genes followed by restriction fragment length polymorphism (RFLP) or sequencing analysis. Giardia was identified in eight farm locations (80% prevalence). Overall, 15/200 (7.5%) animals were positive for infection, only one of which was a cow. Giardia duodenalis genotype E was present in 14 of the animals tested. Zoonotic genotype AI was present in one positive sample. Genotype E and genotype A represented 93% and 7% of G. duodenalis infections, respectively. This study demonstrates that G. duodenalis infection was prevalent in dairy calves in São Paulo state and that the non-zoonotic genotype E predominates in cattle in this region. Nevertheless, calves naturally infected in Brazil can shed Giardia cysts that can potentially infect humans, and thus, they may represent a public health risk. © Institute of Parasitology, Biology Centre ASCR.
Keywords: Cattle; Genotyping; Giardia duodenalis; PCR-RFLP; Sequencing